A novel approach for occupational health risk assessment and its application to the welding project. (10th December 2022) - Li, Yanan; Liu, Wanfang; Chen, Zipeng; Jiang, Luping; Ye, Penghao
Abstract: Occupational health risk assessment (OHRA) is a significant area of interest within the field of environmental and sustainability assessment as well as cleaner production and technical processes. The existing body of research on OHRA suffered from notable methodological weaknesses or failed to consider the complex nature of OHRA in real-world situations. Here, we explore a novel framework for OHRA on the basis of China's Occupational Hazards Classification through the involvement of improved set pair analysis. A case-study approach and comparison analysis were adopted to gain a deeper insight into that model through the application in two manufacturing enterprises, designated as M and N. The results indicated that the health risks caused by high temperature in workshop M was 45.5% at medium risk and 54.5% at high risk. That of noise was 46% at low risk and 54% at medium risk. The integrated risks for both selected welding workshops were assessed at a III level, medium risk. The welding workshop for enterprise N was better than that of enterprise M. The data suggested that a key priority should thus be to plan for reducing the risk caused by total volatile organic compounds. The results of this study support the view that the proposed model may be applicable to the welding industrial process. Greater efforts are strongly recommended in order to test the generalizability of these findings. Taken together, the present results support further development of internal environmental assessment and contributes to related cleaner production. Graphical abstract: Highlights: A novel approach for occupational health risk assessment was proposed based on SPA. Case studies in manufacturing were selected to test the effectiveness of that model. The integrated risks for both welding workshops were at a III level, medium risk. Some targeted interventions were developed on the basis of current findings.